Factors for enhancing OCB (Organizational Citizenship Behavior) - Retno Sri Purwanti; S. . Martono; Vini Wiratno Putri; Angga Pandu Wijaya (Al Tijarah, 2020)
The aim of this study was to examine the effect of work overload and resilience on organizational citizenship behavior through organizational commitment as a mediating variable. The population in this study were education staff of Universitas Negeri Semarang, the number is 774. The sampling technique used in this study was proportionate random sampling technique with a sample of 135 employees. Methods of data collection using questionnaires, observations, interviews, and literature. Methods of data analysis using descriptive statistical tests and SmartPLS 3.0 software. The results showed that work overload had no significant effect on organizational commitment and OCB. Resilience has a significant effect on organizational commitment and OCB. Organizational commitment also has a significant influence on OCB. Meanwhile, organizational commitment has no significant effect in mediating the relationship of work overload on OCB. Then organizational commitment has a significant effect in mediating the relationship of resilience on OCB. The theoretical suggestion for further research is to be able to expand the sample, such as for employees of profit-oriented manufacturing companies. Then practical advice for employees and universities in order to interpret OCB as positive behavior and encourage the implementation of OCB in the workplace to increase organizational effectiveness.